Aux/IAAs: specificity and redundancy - Qiming Wen; Qian Gong; Huaying Yu; Panyu Yang (Plant Signaling & Behavior)
Auxin/Indole-3-Acetic Acids(Aux/IAAs), a class of early auxin-responsive genes, encode short-lived nuclear proteins that play pivotal roles in auxin signaling. In vascular plants, Aux/IAA genes form large families-such as the 29 members in Arabidopsis, exhibiting both functional redundancy and specificity. Canonical Aux/IAA proteins contain four conserved domains and mediate nuclear auxin response by interacting with Transport Inhibitor Response 1/Auxin Signaling F‐box (TIR1/AFB) auxin receptors and Auxin Response Factor (ARF) transcription factors. Loss- and gain-of-function mutants have been instrumental in dissecting the roles of individual Aux/IAAs. Recent studies have also uncovered the mechanism of non-canonical Aux/IAAs, which lack one or more conserved domains and regulate auxin signaling through distinct pathways. This review summarizes the structural features of Aux/IAA proteins, the functional diversity of non-canonical members, the phenotypic effects of their mutants, and their expression patterns. These findings reveal a hierarchical regulatory network of the Aux/IAA gene family in auxin signaling – balancing robustness through functional redundancy and precision and flexibility through member-specific functions in plant growth and development.